A comprehensive review on the effect of process parameters and post-process treatments on microstructure and mechanical properties of selective laser melting of AlSi10Mg - Nandita Limbasiya; Aryan Jain; Harsh Soni; Vishal Wankhede; Grzegorz Krolczyk; Pankaj Sahlot (Journal of Materials Research and Technology, 2022)
Selective Laser Melting (SLM) process has a great potential to create unique 3D components of AlSi10Mg with exceptional degrees of freedom for wide range of applications in industries. However, the presence of porosity and other defects influenced by process parameters can be harmful to fabricated components in some applications. Process parameters and post-processing treatments helps in minimizing the metallurgical defects and enhance the mechanical properties. This review aims to provide a detailed description of the recent research done on the SLM-AlSi10Mg including the effect of SLM process parameters on the mechanical properties of the alloy. The effect of different heat treatments on the microstructure and overall mechanical properties of SLM fabricated AlSi10Mg alloy parts also discussed. The findings of the review revealed that the density of additively manufactured AlSi10Mg built part first increases with increase in energy density and then decreases above threshold value due to lack of fusion at low energy and at high energy key hole formation take place. Tensile strength of the built parts is affected by the process parameters, built direction, baseplate preheating temperature and built environment. The process parameters and built condition also affect the roughness and hardness of additively manufactured AlSi10Mg parts. Heat and surface treatment also help to improve the mechanical and surface properties by changing microstructure orientation. Furthermore, a comprehensive study of various surface finishing techniques based on energy sources such as mechanical, chemical and thermal improves the surface roughness and fatigue life of SLM fabricated AlSi10Mg parts is also presented.